Netscout Threat Intelligence Report 2H 2020. Issue 7 (July 2021) - Unknown
Abstract : Cyber criminals are nothing if not entrepreneurial. They have developed business models that sometimes borrow from mainstream enterprises – such as customer support and special offers – and which occasionally show flashes of originality.